Elements of multimedia used in the Jawi mobile application - Ahmad, Asma’; Mohd Lazim, Nur Aniza; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
Jawi script is derived from the Arabic script and contains six additional characters to represent Malay vowel sounds. Mobile applications incorporate multimedia elements such as text, images, sound, video and animation to enhance learning. This research aims to study and evaluate multimedia components found in Jawi mobile applications. This research focuses on how multimedia elements are used and how important they are to increasing user engagement and learning outcomes. This study uses content analysis to evaluate multimedia elements in a selected sample of Jawi mobile applications. The main finding shows no video content, although other multimedia elements are widely used. This indicates that there is room for improvement in the design of these mobile applications, as video could increase user engagement and Jawi mobile application developers should consider diversifying multimedia components to be more interactive and dynamic.